2022
DOI: 10.1177/02692155221107736
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive resistive monopolar radiofrequency at 448 kHz plus exercising versus exercising alone for subacromial pain: A sham-controlled randomized clinical trial

Abstract: Objective To investigate the effectiveness of thermal and sub-thermal capacitive-resistive monopolar radiofrequency at 448 kHz plus exercising compared to sham radiofrequency plus exercising on pain, functionality, and quality of life in patients with subacromial pain. Design Randomized, controlled, parallel, double-blind, three-arm clinical trial. Setting Hospital and Primary Care. Subjects Eighty-one participants with subacromial pain in three intervention groups. Interventions Three interventions with capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…In contrast, non-pooled data for improvement in function in Akyol’s 2012 study [ 76 ] reported significant changes in favour of the control sham MWD group compared with MWD at post-treatment (MD −2.35, 95% CI −3.50 to −1.20, random-effects model) and short-term follow-up (MD −4.05, 95% CI −5.23 to −2.87, random-effects model). Non-pooled data for improvement in function in Jimenez-Garcia 2008, Rabini 2012, and Avendaño-Coy 2022 [ 59 , 77 , 92 ] did not show any significant changes in favour of any considered groups at any time point ( Table 9 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, non-pooled data for improvement in function in Akyol’s 2012 study [ 76 ] reported significant changes in favour of the control sham MWD group compared with MWD at post-treatment (MD −2.35, 95% CI −3.50 to −1.20, random-effects model) and short-term follow-up (MD −4.05, 95% CI −5.23 to −2.87, random-effects model). Non-pooled data for improvement in function in Jimenez-Garcia 2008, Rabini 2012, and Avendaño-Coy 2022 [ 59 , 77 , 92 ] did not show any significant changes in favour of any considered groups at any time point ( Table 9 ).…”
Section: Resultsmentioning
confidence: 96%
“…Six studies [ 58 , 59 , 76 , 77 , 78 , 92 ] evaluated the efficacy of diathermy for treating STN. Two studies utilized SWD, 3 studies used MWD, and 1 utilized CRET.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants received one 448 kHz CRMR intervention. Each participant was positioned in a supine posture with their knees flexed at an angle of 20 degrees [ 18 ]. Utilizing the INDIBA ® Activ 8 apparatus, characterized by a peak power of 200 W and 450 VA, continuous radiofrequency electromagnetic radiation (CRMR) at 448 kHz was administered, consistent with previous investigations [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The application of capacitative-resistive monopolar radiofrequency (CRMR) at 448 kHz in healthy subjects has been shown to be more effective than conventional thermotherapy at an increasing temperature in superficial and deep tissues and also blood flow in both skin and deep tissues, as well as increasing hemoglobin saturation [ 14 , 17 ]. Radiofrequency adaptations to hyperthermia are based on vasodilation, which causes increased local blood perfusion and reduced muscle tension and spasm, increasing oxygen and nutrients as well as accelerating the healing process [ 18 ]. CRMR shows an ability to improve pain, function, and quality of life in patients with musculoskeletal disorders, especially spinal disorders and knee osteoarthritis [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%